Pengaruh Kesetaraan Gender Terhadap Pendapatan Perkapita di Kabupaten Gorontalo Tahun 2014 – 2023 - Fatma Dangi; Meimoon Ibrahim; Moh.Arif Novriansyah (Pusat Riset dan Inovasi Nasional, 2025)
This research focuses on understanding how gender equality impacts per capita income in Gorontalo Regency. A quantitative method was used, relying on secondary data for analysis. To explore the connection between gender equality and per capita income, simple linear regression was applied. The results indicate that gender equality positively and significantly influences per capita income in this area. The analysis showed a determination coefficient, which reveals that 81. 3 percent of the change in per capita income is accounted for by gender equality, while the remaining 18. 7 percent is affected by other factors that are not considered in this study. This implies that enhancing gender equality plays a crucial role in boosting per capita income within Gorontalo Regency..